A Value Chain Analysis on The Business Development - Al Hamidi, Muhammad Faiz; Hapsari, Raditha Dwi Vata (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to identify and analyze the primary and support activities within the value chain of Patperempat, a bottled milk coffee business, and to examine how value chain analysis can support business development and competitive advantage. Design/Methodology/Approach – This study adopts a qualitative case study approach using value chain analysis as the primary analytical framework. Data were collected through interviews, observations, and document analysis involving the company's internal stakeholders, customers, and prospective customers. The analysis focused on evaluating the effectiveness of primary and support activities and identifying strategic opportunities for business development. Findings – The findings indicate that Patperempat's primary value chain activities have been implemented effectively, whereas its support activities remain underdeveloped and require significant improvement. Based on the value chain analysis, the business is best positioned to adopt a differentiation strategy by emphasizing product variation and continuous innovation. Strengthening support activities is expected to enhance operational capability, reinforce competitive positioning, and support sustainable business growth. Originality/Value This research is original in applying value chain analysis to a pre-order bottled coffee business model. The findings provide practical value by identifying specific improvement opportunities to support a differentiation strategy through innovation and product variation.